2019
DOI: 10.1039/c8fd00114f
|View full text |Cite
|
Sign up to set email alerts
|

A neuromorphic systems approach to in-memory computing with non-ideal memristive devices: from mitigation to exploitation

Abstract: Memristive devices represent a promising technology for building neuromorphic electronic systems. In addition to their compactness and non-volatility features, they are characterized by computationally relevant physical properties, such as state-dependence, non-linear conductance changes, and intrinsic variability in both their switching threshold and conductance values, that make them ideal devices for emulating the bio-physics of real synapses. In this paper we present a spiking neural network architecture t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 65 publications
0
73
0
Order By: Relevance
“…The impact of the dynamical model of the memristor has been studied in the implementation of STDP, and the learning rules can be adapted to the different behaviors. As in most application of memristors as non-volatile storage of (synaptic) weights, it suffers from the intrinsic variability of the units, which more general neuromorphic circuits are able to exploit [64].…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…The impact of the dynamical model of the memristor has been studied in the implementation of STDP, and the learning rules can be adapted to the different behaviors. As in most application of memristors as non-volatile storage of (synaptic) weights, it suffers from the intrinsic variability of the units, which more general neuromorphic circuits are able to exploit [64].…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…[28] is adopted. Though our proposed architecture and learning method are demonstrated by simulation, the used models and parameters are set according to experimental results [1,2,7,11]. Parameters for simulation are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These systems use memristors as synapses to store synaptic weights and implement multiplication and addition by physical processes, which are energy-efficient. For instance, Payvand et al proposed a neuromorphic system with non-ideal memristive devices and demonstrated the system using behavioral simulation [7]. There are mainly two kinds of memristive neuromorphic computing systems: voltage-based systems and spike-based systems [1,2,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…SNN and artificial neural network systems that utilize memristors as their learning components or simply as a programmable element have been researched extensively . Here, we mainly focus on neuromorphic systems that utilize SiO x memristive devices for learning, where memristors are used as weight elements.…”
Section: Neuromorphic Systems Designmentioning
confidence: 99%